First records of presocial behavior of Montezumia brethesi Bertoni, 1918 (Hymenoptera, Vespidae, Eumeninae) - Lopes, R. B. [UNESP]; Noll, F. B. [UNESP] (Springer, 2019)
Montezumia Saussure is a genus of mason wasps with diverse nesting habits that occurs in the New World. Although all make nests of mud, these can be built as pots above ground or within galleries. Here, observations on nesting and provisioning in M. brethesi are made for the first time and strongly suggest communal nesting. This agrees with previous observations on M. cortesioides, but contrasts with reports from M. pelagica, a supposedly closely related species.
Keywords: Sociality; Mud nests; Odynerini; Progressive provisioning; Parental care